Characterization of endophytic Streptomyces strains from roots of cocoyam (Xanthosoma sagittifolium L. Schott) in the South West Region of Cameroon, their in vitro plant growth promoting abilities and biocontrol efficacy against Pythium myriotylum - Djuidje, P. F. Kouomou; Asultan, W.; Beaulieu, C.; Wong, M. Y.; Boudjeko, T. (Elsevier, 2022)
The focus of this study was to isolate, evaluate and characterize endophytic actinobacteria from cocoyam roots collected in the localities around Mount Cameroon for their potential antagonistic activities against Pythium myriotylum (the major pathogen that limits growth and productivity of this crop in Cameroon) and their ability to promote plant growth. A total of 171 actinobacteria were isolated from healthy cocoyams and were screened for their antagonistic activities against P. myriotylum, Phytophthora megakarya, Fusarium oxysporum and Colletotrichum gloeosporioides. Four isolates (PERM1, PERM2, PERM4 and PERM5) were selected based on of their strongest antagonistic activity in vitro against P. myriotylum. These four isolates were subsequently identified using phenotypic and molecular tests, characterized for extracellular hydrolytic enzymes, plant growth-promoting (PGP) traits, and their effects were evaluated on tissue culture-derived cocoyam plantlets. The sequencing of the 16S rRNA genes and alignment with sequences retrieved through the EzTaxon program indicated that PERM2, PERM4 and PERM5 have low similarity percentages with S. samsunensis EU077190 (92.4% sequence similarity), S. roietensis KX394336 (81% sequence similarity), S. flavoviridis AB184842 (91% sequence similarity) respectively. The comparison of some physiological and biochemical properties of PERM2,PERM4 and PERM5 with the most closely related Streptomyces species showed that these strains differ phenotypically. PERM2, PERM4 and PERM5 might represent new species. All selected Streptomyces were able to produce siderophores, indole-3-acetic acid (IAA), aminocyclopropane-1-carboxylate (ACC) deaminase, and solubilized tricalcium phosphate. With 20.30 μg/ml of IAA, the PERM2 isolate significantly increased the length of roots as compared to the positive control. These results suggest the possibility of using endophytic Streptomyces strains, especially isolate PERM2 in the protection of cocoyams against root rot disease and the promotion of root growth.